Facile preparation of N-doped graphene quantum dots as quick-dry fluorescent ink for anti-counterfeiting. (27th September 2018) - Pang, Youyou; Zhao, Rujian; Lu, Yao; Liu, Jiyang; Dong, Xiaoping; Xi, Fengna
Abstract : N-GQDs are synthesized using a simple and fast one-step protocol and applied for preparing quick-dry fluorescent ink for both writing and printing. Abstract : Simple anti-counterfeiting printing using biocompatible, non-toxic and highly efficient luminescent materials plays crucial roles in economic and social fields as well as in our daily lives. In this work, new nitrogen doped graphene quantum dots (N-GQDs) are synthesized and applied in the preparation of quick-dry fluorescent ink for both writing and printing. The N-GQDs are synthesized based on a one-step bottom-up molecular fusion between 1, 3, 6-trinitropyrene and triethylamine by a solvothermal process with a high yield of 84.6%. Triethylamine simultaneously acts as a reaction medium and a nitrogen-doping agent for the formation of fluorescent N-GQDs. The as-prepared N-GQDs exhibit a single-layer graphene structure, high crystallinity, uniform size and excitation-independent fluorescence emission with a narrow half-peak width (66 nm). Successful doping of N atom in GQDs enables bright blue fluorescence with a high absolute photoluminescence quantum yield (17.8%). Owing to their excellent photostability and good solubility in ethanol, N-GQDs are applied to easily prepare quick-dry fluorescent ink for both writing and printing by simply blending GQDs with glycerol in an ethanol medium. Moreover, synthesis of a fluorescent powder and hydrogel is also achieved.